Improvement in in vitro growth rates of Ganoderma species with industrial wood waste supplements - Alizadeh, Fahimeh; Abdullah, Siti Nor Akmar; Khodavandi, Alireza; Chong, Pei Pei (Academic Journals, 2013)
The bracket-like polypore fungi of the genus Ganoderma, as a pathogen of oil palm (Elaeis guineensis Jacq.), is a major concern primarily because it plays a significant role in the economy of many countries in South-East-Asia. Growth of several Ganoderma isolates was examined on various culture media to develop a medium for rapid growth. Growth analyses revealed that growth of the different isolates was different on various culture media which differed in their nutrient composition and their growth levels were influenced by industrial wood waste. High rate of growth was achieved on rubber/oil palm wood extract agar. Potato dextrose agar supplemented with wood powder and peptone also favoured mycelial growth. Malt extract agar was the poorest among the media investigated for obtaining rapid mycelial growth of Ganoderma isolates. G. boninense PER 71, G. tornatum POR 57 and G. subamboinense var. laevisporium (ATCC 52419) presented higher growth rate on the different culture media. The G. boninense PER 71 showed the fastest growth on the different media, while the minimum growth was achieved for G. tornatum POR 54. Rubber/oil palm wood extract agar media appears to increase growth rate of the different Ganoderma isolates. Increase growth rate of different Ganoderma isolates by industrial wood waste suggested that industrial wood waste is sufficient to improve mycelial growth of Ganoderma isolates. Supporting the assumption, industrial wood waste could be a useful renewable source for the early detection of Ganoderma disease that will improve efforts to prevent economic losses in oil palm. Our rapid and less expensive culture media may also have commercial potential and novel biotechnological applications.